PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN, PERSEPSI TARIF PAJAK DAN MOTIVASI MEMBAYAR PAJAK TERHADAP KEPATUHAN MEMBAYAR PAJAK PADA WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA GIANYAR - Ni Luh Putu Juliana Asih Ikaraini; Komang Fridagustina Adnantara (Journal Research of Accounting, 2021)
This study aims to determine the effect of understanding tax regulations, perceptions of tax rates, and motivation to pay taxes on tax compliance with individual taxpayers at KPP Pratama Gianyar. Taxes have a big role for state revenue, so the government must make efforts to maximize revenue from the tax sector. Besides that, it also requires high compliance for taxpayers to fulfill their tax obligations. The population in this study is an individual taxpayer who is registered at KPP Pratama Gianyar. The sample in this study was 100 taxpayers. The method of collecting data using a questionnaire. The questionnaire was tested for validity and reliability before collecting research data. The data analysis method used is multiple linear regression analysis. The results of this study indicate the understanding of tax regulations, perceptions of tax rates, and motivation to pay taxes have a positive and significant effect on tax compliance with individual taxpayers at KPP Pratama Gianyar. The value of the coefficient of determination (Adjusted R Square) in this study was 0.835, which means that the Tax Paying Compliance variable was influenced by 83.5% by the variables tested in this study, the rest was influenced by other variables outside of this study.